Estimating and Comparing the Implied Cost of Equity for Canadian and U.S. Firms - Witmer, Jonathan; Zorn, Lorie (Bank of Canada, 2007)
This paper estimates the implied cost of equity for Canadian and U.S. firms using a methodology based on the dividend discount model and utilizing firms' current stock price and analysts' forecasted earnings. We find that firm size and firm stock liquidity are negatively related to cost of equity, while greater firm financial leverage and greater dispersion in analysts' earnings forecasts are associated with a higher cost of equity. Moreover, longer-term sovereign bond yields also seem to play a role in a firm's cost of equity. After controlling for several factors, both at a firm-level and at an aggregate level, we find that the cost of equity for Canadian firms is 30-50 bps higher than that of U.S. firms during 1988-2006. Because our estimates may not fully account for factors such as currency risk, inflation uncertainty, degree of market integration, personal taxes, and differences in regulatory environments, we might shed further light on these results by incorporating proxies for these factors and perhaps extending our comparison to more countries.

En faisant appel à une méthodologie basée sur le modèle d'actualisation des dividendes et en exploitant des données relatives au prix actuel des actions et aux bénéfices anticipés par les analystes, les auteurs estiment le coût implicite des capitaux propres des firmes canadiennes et américaines. Ils constatent que la taille des sociétés et la liquidité des actions varient en sens inverse du coût des capitaux propres, alors que l'ampleur de l'endettement des entreprises et de la dispersion des prévisions de profits émanant des analystes est en relation positive avec des coûts élevés. Il semble, en outre, que les rendements des obligations d'État à long terme aient une incidence au chapitre du coût des fonds propres. Après avoir pris en compte plusieurs facteurs à l'échelle des entreprises individuelles aussi bien qu'au niveau agrégé, les auteurs concluent que le coût des capitaux propres des firmes canadiennes dépasse de 30 à 50 points de base celui supporté par les entreprises américaines entre 1988 et 2006. Comme l'étude peut ne pas tenir pleinement compte de facteurs tels que le risque de change, l'incertitude liée à l'inflation, le degré d'intégration des marchés, l'impôt des particuliers et les différences entre les cadres réglementaires, il pourrait s'avérer utile d'incorporer des variables d'approximation à l'égard de ces facteurs et, peut-être, d'étendre la comparaison à d'autres pays.